Associations of state or trait dissociation with severity of psychopathology in young people with borderline personality disorder - Salmon, Ashleigh P.; Nicol, Katie; Kaess, Michael; Jovev, Martina; Betts, Jennifer K.; Chanen, Andrew M. (Borderline Personality Disorder and Emotion Dysregulation, 2023)
State and trait dissociation are associated with borderline personality disorder (BPD) severity and severity of commonly co-occurring mental health symptoms. Although these distinct constructs do not consistently co-occur in experimental settings, they are frequently reported as the same construct, namely dissociation. This study aimed to investigate the co-occurrence of state and trait dissociation among young people with BPD and to examine whether state or trait dissociation were associated with symptom severity in this population.